Gestão escolar e o perfil do diretor de escola na Rede Municipal de Ensino de São Paulo: uma contribuição aos estudos sobre teoria da gestão escolar - Souza, Maria Isabel Vieira de (2022)
This is a study on School Management and the profile of the School Director of the Municipal Education Network of São Paulo (RME-SP) and, to rescue the history of School Management in this Network, a bibliographic review was carried out from 1935 to 1935. 2020, linked to a demographic survey with 1,374 School Directors who worked in 2019 and 2020 in the direct Educational Units of RME-SP, revealing three models of School Management: Traditional, Democratic and Managerial, which made it possible to verify the current profile of the School Director in this network. It started from the hypothesis that the government, when organizing the educational system through regulation or regulation, organizes the forms of Management and promotes a certain ideal type of manager, establishing the limits of the Director's performance and role, so that studying the profile of school principals and the management models produced by public policy can help to understand the consequences of this policy for the quality of education promoted by the State and provide data and information for further studies, collaborating with research in the field. Despite being determined, a deterministic position was not assumed here, given the potential of the organizational culture endogenously built by the School Director in the discretionary exercise in the meanders of creative, purposeful school life, excluding entrepreneurial perspectives of neoliberal appeal. The concepts of Ball, Bowe and Gold (1992) on the Policy Cycle were used, seeking to locate the context of influence, that of text production and the context of practice, the meso approach, suggested by Nóvoa (1992), which prioritizes the school as a place of research, the concept of regulation proposed by J. Barroso (1995), discussing the role of the State in the regulation of education, namely with regard to the maintenance of the ideal of the public school and its commitment to the distribution equitable common good education. The models of public school management were investigated from the relationship with the public administration of the State, the reform of the State (BRESSER-PEREIRA, 1995-1998), and with the General Theory of Administration (CHIAVENATO, 1993/2008) used in the companies , exposing a social, economic and political panorama, drawing a parallel between the organization of the Brazilian public service in the Patrimonial, Bureaucratic and Managerial models and the organization of the School Management models: Traditional, Democratic and Managerial. The dissemination of the accountability policy, in the neoliberal perspective, generated the responsibility of School Directors for school failure, linked to a discourse of inefficiency of the public service. The Municipal Education Network of São Paulo is influenced by the three models, even though the legally assumed model is that of Democratic Management. Since 1995, the State has been introducing the Management model and, until today, there are remnants of Traditional administration